Drupal's building blocks : quickly building websites with CCK, Views and Panels - Miles, Earl (Addison-Wesley Professional, 2009)
Using Drupal, web professionals can create full-featured websites with just a few clicks. Drupal's core is compact and well documented, but much of Drupal's immense power lies elsewhere: in external modules that, until now, have not been well documented. Now, however, there's Drupal's Building Blocks, an authoritative tutorial, reference, and cookbook for Drupal's most valuable modules. The authors are Drupal insiders who've spent years creating and supporting these modules-Earl Miles, developer of the Views module, and Lynette Miles, Drupal documentation team member. They've brought together indispensable, up-to-date information you won't find anywhere else, as well as extensive sample "recipe" code designed for easy adaptation and reuse. Learn how to Use Content Construction Kit (CCK) to customize your data around your needs Improve site flexibility with Drupal's node system Add optional field types, including PHP-based fields Use modules with themes to display data more attractively and legibly Build powerful Views query displays Integrate with SQL databases Customize Views with relationships, arguments, and filters Optimize query performance Add styling through the Panel UI or custom-code-based designs Maintain full control over sites as you deploy into production This book will help you create more powerful, flexible, usable, and manageable websites--whether you're a web developer, designer, administrator, architect, or consultant. About the Website The accompanying website contains all examples, code, and themes presented in this book